Made in America: Why the Shale Revolution in America is Not Replicable in China and Argentina - Danelle Gagliardi (Washington University Global Studies Law Review, 2015)
In this Note, I argue that the economic prosperity and apparent success the United States has experienced (“the boom”) in drilling shale will not be replicated in China, where the shale reserves are estimated to be significantly larger than in the United States. Many have claimed the shale boom in the United States is unique, but none have articulated specifically why China will not be able to generate the immediate and continuous prosperity the United States has had. Legal factors distinctive to the United States, such as private ownership of mineral rights; well-established environmental and regulatory mechanisms; contract law principles; and a free market system demonstrate that China—which has recently commenced exploration and production of shale domestically—will not be able to replicate the economic boom the United States has seen with shale development in the past two years. There is a glimmer of hope, however, for the country of Argentina, which has a hybrid of regulatory, contract, and property laws between those of China and the United States, possibly opening the door for a successful shale revolution in the future.
Keywords: shale; fracking; oil; energy; clean energy; boom; environment; drilling; China; Argentina; United States